Stakeholders Awareness of Safety Leadership Through Construction Safety Management System in Indonesia - Desiderius Viby Indrayana; Akhmad Suraji (Applied Research on Civil Engineering and Environment (ARCEE), 2021)
Construction workplace safety has become serious issues among global companies. Improvement on occupational safety and health has been carried out. However, construction still becomes a sector with the highest accident rate. Particularly in Indonesia, construction contributes to 32% of accident rate followed by transportation, forestry, and mining. Main driver to improve safety performance is safety leadership as the frontline part of Construction Safety Management System (CSMS). Since it is a non-technical aspect, stakeholders’ awareness is doubtful. Therefore, this study aims to describe Indonesia construction stakeholders’ awareness of safety leadership as part of CSMS. Questionnaire was distributed to 693 respondents comprises of government, planners, consultants, private contractors, and State-Owned Enterprise (SOE) contractors. The result was analyzed with descriptive statistic to reveal the stakeholders’ level of awareness. SOE contractor has the highest awareness of safety leadership. It is considered as obvious finding since SOE contractor becomes dominant in Indonesia’s construction industry. The majority of big-classified contractors are SOE. Meanwhile, contractors’ BOD is the lowest. The BOD commonly uses managerial leadership to run the company rather than safety leadership. However, the safety leadership should be owned by every stakeholder in construction industry whether they are in high or low management level.